The Solomon R. Guggenheim Museum : a Selection from the Museum Collection. - Morris, J.A.; Shadbolt, Doris (Vancouver : Vancouver Art Gallery, 1954)
Calder, Alexander ; Campendonk, Heinrich ; Chagall, Marc ; Feininger, Lyonel ; Gabo, Naum ; Gleizes, Albert ; Gris, Juan ; Hartley, Marsden ; Kandinsky, Wassily ; Kirchner, Ernst Ludwig ; Klee, Paul ; Leger, Fernand ; Marc, Franz ; Matisse, Henri ; Metzinger, Jean ; Miro, Joan ; Modigliani, Amedeo ; Moholy-Nagy, Laszlo ; Mondriaan, Piet ; Pevsner, Antoine ; Picasso, Pablo ; Schwitters, Kurt ; Seurat, Georges ; Severini, Gino ; Vordemberge-Gildewart, Friedrich ; Xceron, Jean
Engels
The Solomon R. Guggenheim Museum : a Selection from the Museum Collection, Vancouver Art Gallery, Vancouver, November 16th to December 12th, 1954
kunstcatalogus